2014
DOI: 10.1161/strokeaha.114.005018
|View full text |Cite
|
Sign up to set email alerts
|

Lacunar Strokes in Patients With Diabetes Mellitus: Risk Factors, Infarct Location, and Prognosis

Abstract: Background and Purpose Diabetes is an independent risk factor for lacunar strokes. Few data are available regarding patient features, infarct location, and recurrent vascular events for diabetic patients with lacunar stroke. Methods We compared features at study entry and prognosis during 3.6 years of follow-up of diabetic vs. non-diabetic patients with recent lacunar stroke participating in the Secondary Prevention of Small Subcortical Strokes (SPS3) randomized trial. Results Among the 3020 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 15 publications
5
53
1
5
Order By: Relevance
“…Regarding cerebral SVD, an increased prevalence of lacunar infarcts has been described in subjects with type 2 diabetes compared with subjects without DM (23). Further, patients with diabetes and lacunar strokes show a poorer prognosis than their nondiabetic counterparts (9). In our study, the frequency of lacunes was lower than those in previous studies, because our patients had no history of cerebrovascular disease.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Regarding cerebral SVD, an increased prevalence of lacunar infarcts has been described in subjects with type 2 diabetes compared with subjects without DM (23). Further, patients with diabetes and lacunar strokes show a poorer prognosis than their nondiabetic counterparts (9). In our study, the frequency of lacunes was lower than those in previous studies, because our patients had no history of cerebrovascular disease.…”
Section: Discussioncontrasting
confidence: 57%
“…Lacunar infarcts or lacunes are small noncortical infarcts caused by the occlusion of small penetrating branches of large cerebral arteries. Several studies (9) have shown that diabetes is an independent risk factor for lacunar strokes. Finally, in patients with diabetes, the presence and severity of retinopathy are associated with future CV events, including ischemic stroke (10,11).…”
mentioning
confidence: 99%
“…However, the severity and type of hypertension differed across studies. For example, 1 study recruited patients who had been diagnosed with hypertension for at least 1 year and did not further restrict based on severity (18). However, >70% of the participants were already controlled on medication at study initiation.…”
Section: Results: Part 1 Study Characteristicsmentioning
confidence: 99%
“…[17][18][19][20] In particular, DM predicted stroke recurrence in the settings of lacunar stroke and large artery atherosclerosis. 19,20 Our data first show that DM could be a risk factor for recurrent vascular events in ESUS patients with any underlying embolic causes. On the contrary, we show that the CAM score, based on the degree of aortic arch calcification on chest radiograph, age, and multiple brain infarcts, is independently associated with recurrent vascular events in patients with ESUS.…”
Section: Discussionmentioning
confidence: 99%